Log in to add a comment

## Answers

let y = x² + 4x - 12 / x - 2

Step 1:

Divide the first term of the dividend to that of the first term of the divisor.

x² / x = x

The quotient will be the first term of your answer.

Step 2:

Multiply first the quotient by the terms of the divisor.

x(x) = x²

x(-2) = -2x

And then put it below the terms of the dividend.

Step 3:

Subtract the terms of the divisor by the product.

x² - x² = 0

4x - (-2x) = 6x

Step 4:

Bring down one term left next to the difference.

6x - 12

Step 5:

Then go, repeat to step 1.

**y = x + 6**

Now, can you get it? :)

Now, can you get it? :)